EVALUATING AND COMPARING THE POTENTIAL ENVIRONMENTAL IMPACTS FROM THE PRODUCTION OF DIESL AND LIQUEFIED PETROLEUM GAS, AL-DAURA REFINERY, BAGHDAD, IRAQ - Ali Alanbari, Mohammad; Rahman Ghanem, Israa (Journal of Engineering and Sustainable Development, 2018)
Petroleum is the main source of energy in the world, plays an important role in human life, but also its have many environmental impacts. Various software's are designed to focus on the environmental impacts of Petroleum production and accomplish the assessment, one of these software's is SimaPro software package which is designed to make a valuable contribution. It is an essential tool for analyzing the environmental impact of products during their whole life cycle. A huge amount of knowledge about the environment is built into the program and database, enabling to analyze a product with a minimum of specialized knowledge. In this study, SimaPro7 is used to analyze and evaluate the impacts for AL-Daura refinery for the Diesel and LPG (liquefied petroleum gas) fuel production .The results of LCA are not mostly straightforward in favor of material design over the alternative one. The IMPACT2002+ methodology is used for evaluating the products. This method has proved to be a powerful tool for designers to aggregate LCA results in easily and understandable form. The results of Life Cycle Assessment (LCA) show that Diesel has an impact and damage on the environment (single score) of the order of 0.300302 point for each 1 cubic meter producing from Diesel fuel while LPG has a single score of 0.191243, (The "Single Score" variable is measured in units of points (Pt), which indicates the potential number of people affected by the environmental impacts taken into consideration a period of one year).